A Study on the creative industry as a pillar of sustained growth and diversification : the film and music sectors in Jamaica - lessons from case studies of successful firms and ventures - Hendrickson, Michael (UN ECLAC SantiagoCL, 2018)
Identifies the critical success factors that have resulted in the global competitiveness and sustainability of individuals, firms and ventures within the music and film subsectors in Jamaica.